Monitoring Cochlear Health With Intracochlear Electrocochleography During Cochlear Implantation: Findings From an International Clinical Investigation. Issue 2 (8th November 2022) - O'Leary, S.; Mylanus, E.; Venail, F.; Lenarz, T.; Birman, C.; Di Lella, F.; Roland, J. T.; Gantz, B.; Beynon, A.; Sicard, M.; Buechner, A.; Lai, W. K.; et al.
Abstract : Objectives: Electrocochleography (ECochG) is emerging as a tool for monitoring cochlear function during cochlear implant (CI) surgery. ECochG may be recorded directly from electrodes on the implant array intraoperatively. For low-frequency stimulation, its amplitude tends to rise or may plateau as the electrode is inserted. The aim of this study was to explore whether compromise of the ECochG signal, defined as a fall in its amplitude of 30% or more during insertion, whether transient or permanent, is associated with poorer postoperative acoustic hearing, and to examine how preoperative hearing levels may influence the ability to record ECochG. The specific hypotheses tested were threefold: (a) deterioration in the pure-tone average of low-frequency hearing at the first postoperative follow-up interval (follow-up visit 1 [FUV1], 4 to 6 weeks) will be associated with compromise of the cochlear microphonic (CM) amplitude during electrode insertion (primary hypothesis); (b) an association is observed at the second postoperative follow-up interval (FUV2, 3 months) (secondary hypothesis 1); and (c) the CM response will be recorded earlier during electrode array insertion when the preoperative high-frequency hearing is better (secondary hypothesis 2). Design: International, multi-site prospective, observational, between groups design, targeting 41 adult participants in each of two groups, (compromised CM versus preserved CM). Adult CI candidates who were scheduled to receive a Cochlear Nucleus CI with a Slim Straight or a Slim Modiolar electrode array and had a preoperative audiometric low-frequency average thresholds of ≤80 dB HL at 500, 750, and 1000 Hz in the ear to be implanted, were recruited from eight international implant sites. Pure tone audiometry was measured preoperatively and at postoperative visits (FUV1 and follow-up visit 2 [FUV2]). ECochG was measured during and immediately after the implantation of the array. Results: From a total of 78 enrolled individuals (80 ears), 77 participants (79 ears) underwent surgery. Due to protocol deviations, 18 ears (23%) were excluded. Of the 61 ears with ECochG responses, amplitudes were < 1 µV throughout implantation for 18 ears (23%) and deemed "unclear" for classification. EcochG responses >1 µV in 43 ears (55%) were stable throughout implantation for 8 ears and compromised in 35 ears. For the primary endpoint at FUV1, 7/41 ears (17%) with preserved CM had a median hearing loss of 12.6 dB versus 34/41 ears (83%) with compromised CM and a median hearing loss of 26.9 dB ( p < 0.014). In assessing the practicalities of measuring intraoperative ECochG, the presence of a measurable CM (>1 µV) during implantation was dependent on preoperative, low-frequency thresholds, particularly at the stimulus frequency (0.5 kHz). High-frequency, preoperative thresholds were also associated with a measurable CM > 1 µV during surgery. Conclusions: Our data shows that CM drops occurring during electrode insertion were correlated with significantly poorer hearing preservation postoperatively compared to CMs that remained stable throughout the electrode insertion. The practicality of measuring ECochG in a large cohort is discussed, regarding the suggested optimal preoperative low-frequency hearing levels ( < 80 dB HL) considered necessary to obtain a CM signal >1 µV.